Rotating Machinery, Hybrid Test Methods, Vibro-Acoustics & Laser Vibrometry, Volume 8 Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 - Di Maio, Dario; Castellini, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Rotating Machinery, Hybrid Testing, Vibro-Acoustics & Laser Vibrometry, Volume 8: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the eighth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Rotating Machinery, Hybrid Testing, Vibro-Acoustics & Laser Vibrometry, including papers on: Rotating Machinery Vibro-Acoustics Experimental Techniques Advances in Wind Energy Scanning Laser Doppler Vibrometry Methods Hybrid Test Methods.
Chapter 1. Strategies for Testing Large Aerospace Structures with 3D SLDV -- Chapter 2. Modal Model Validation Using 3D SLDV, Geometry Scanning and FEM of a Multi-Purpose Drone Propeller Blade -- Chapter 3. Effect of Dry Friction Damping on the Dynamic Response of Helicopter Tail Shaft -- Chapter 4. Nonlinear Dynamic Analysis of a Spiral Bevel Geared System -- Chapter 4. Estimating Material Wave speed Using the Wave number Transform of Rectangular Plate Mode Shapes -- Chapter 5. In-Operation Wind Turbine Modal Analysis via LPV-VAR Modeling -- Chapter 6.Structural Damage Identification Using Free Response Measured by a Continuously Scanning Laser Doppler Vibrometer System -- Chapter 7. Mitigation of Structural-Acoustic Mode Coupling in a Modal Test of a Hollow Structure -- Chapter 8. Application of 3D Scanning Laser Doppler Vibrometry to an Article with Internal Features -- Chapter 9.The Measurement of a Nonlinear Resonant Decay using Continuous-scan Laser Doppler Vibrometry -- Chapter 10. Vibro-Acoustic Modulation of a Spinning Apparatus for Nondestructive Evaluation -- Chapter 11. Nonlinear Phase Separation Testing of an Experimental Wing-Engine Structure -- Chapter 12. Wind Turbine Health Monitoring: Current and Future Trends with an Active Learning Twist -- Chapter 13. Nonlinear 3D Dynamic Model of an Automotive Dual Mass Flywheel -- Chapter 13. Investigation of Notch-type Damage Identification by Using a Continuously Scanning Laser Doppler Vibrometer System.
Keywords: Machinery; Aerospace engineering; Astronautics; Multibody systems; Vibration; Mechanics, Applied; Engines; Control engineering; Robotics; Automation; Machinery and Machine Elements; Aerospace Technology and Astronautics; Multibody Systems and Mechanical Vibrations; Engine Technology; Control, Robotics, Automation